Iron chelation and 2-oxoglutarate-dependent dioxygenase inhibition suppress mantle cell lymphoma's cyclin D1 - Babosova, Olga; Kapralova, Katarina; Raskova Kafkova, Leona; Korinek, Vladimir; Divoky, Vladimir; Prchal, Josef T; Lanikova, Lucie (Journal of cellular and molecular medicine, 2019)
The patients with mantle cell lymphoma (MCL) have translocation t(11;14) associated with cyclin D1 overexpression. We observed that iron (an essential cofactor of dioxygenases including prolyl hydroxylases [PHDs]) depletion by deferoxamine blocked MCL cells' proliferation, increased expression of DNA damage marker γH2AX, induced cell cycle arrest and decreased cyclin D1 level. Treatment of MCL cell lines with dimethyloxalylglycine, which blocks dioxygenases involving PHDs by competing with their substrate 2-oxoglutarate, leads to their decreased proliferation and the decrease of cyclin D1 level. We then postulated that loss of EGLN2/PHD1 in MCL cells may lead to down-regulation of cyclin D1 by blocking the degradation of FOXO3A, a cyclin D1 suppressor. However, the CRISPR/Cas9-based loss-of-function of EGLN2/PHD1 did not affect cyclin D1 expression and the loss of FOXO3A did not restore cyclin D1 levels after iron chelation. These data suggest that expression of cyclin D1 in MCL is not controlled by ENGL2/PHD1-FOXO3A pathway and that chelation- and 2-oxoglutarate competition-mediated down-regulation of cyclin D1 in MCL cells is driven by yet unknown mechanism involving iron- and 2-oxoglutarate-dependent dioxygenases other than PHD1. These data support further exploration of the use of iron chelation and 2-oxoglutarate-dependent dioxygenase inhibitors as a novel therapy of MCL.
Keywords: mantle cell lymphoma; protein FOXO3; DNA Damage; Hydroxylation; Cell Hypoxia; Cell Line, Tumor; cyklin D1; iron; prolyl hydroxylases (EGLN/PHDs); dioxygenasy; deferoxamin; Deferoxamine; Enzyme Inhibitors; lidé; Hypoxia-Inducible Factor-Proline Dioxygenases; Iron Chelating Agents; lymfom z plášťových buněk; messenger RNA; Lymphoma, Mantle-Cell; 2-oxoglutarate-dependent enzymes; Dioxygenases; DNA damage; prolyl-4-hydroxylasy HIF; deficit železa; RNA, Messenger; Cyclin D1; Down-Regulation; poškození DNA; Amino Acids, Dicarboxylic; inhibitory enzymů; cell cycle; down regulace; hydroxylace; Ketoglutaric Acids; Forkhead Box Protein O3; chelátory železa; kyseliny ketoglutarové; Iron Deficiencies; aminokyseliny dikarboxylové; hypoxie buňky; nádorové buněčné linie; Humans